Supplementary feed potential on histology and immune response of tilapia (Oreochromis niloticus L.) exposed to microplastics - Hayati, Alfiah; Pramudya, Manikya; Soepriandono, Hari; Suhargo, Listijani; Dewi, Firli Rahmah Primula; Muchtaromah, Bayyinatul; Mwendolwa, Adamu Ayubu (Penerbit Universiti Kebangsaan Malaysia, 2023)
Polyester microplastics (PS) are toxic and hazardous chemicals in the ecosystem that can induce stress. Disposing PS articles into the environment can negatively impact health of aquatic biota, including fish. This study aimed to investigate the potential of probiotics or vitamin C supplementation in improving the histological structure of organs and cytokine secretion in tilapia fish exposed to PS. Thirty-six tilapia were divided into 12 groups consisting of treatment groups (four PS concentration variations: 0, 0.1, 1, and 10 mg/L). Each treatment was given three types of feed: Commercial feed alone, commercial feed containing probiotics (200 mL/kg), and commercial feed containing vitamin C (100 mg/kg). The study had a sample size of n=3. After treatment was completed, all parameters were measured. The result showed that the addition of probiotics and vitamin C could decrease TNF-α levels and increase IFN-γ levels. Probiotics and vitamin C prevent healthy cells to be damaged by pro-inflammatory cytokines. The percentage of normal hepatocytes increased significantly in all treatment groups with the addition of probiotics or vitamin C. Furthermore, the percentage of hepatocytes with swelling and necrosis decreased significantly in treatment groups (p < 0.05). Additionally, villi height, lamina propria width, submucosa height, and the number of goblet cells all increased significantly in all treatment groups with the administration of probiotics or vitamin C (p < 0.05). Overall, both probiotics and vitamin C supplements have the potential to maintain fish health. Vitamin C exhibits a greater potential than probiotics in regulating immune responses. Meanwhile, both probiotics and vitamin C supplements have potential to inhibit damage to the hepatic and intestine structures of fish exposed to PS.